Operational Management for Business Production Processes - Tambunan, Hotbona Novandi; Haribowo, Rio; Akbar, Akbar; Munizu, Musran; Pandiangan, Saut Maruli Tua (LPPPIPublishing, 2025)
The purpose of this study is to provide an explanation of the theory of operational management related to the production process in a company. To achieve this goal, the research method used is a literature study approach and a theory development approach based on the work of Richar L. Darft on operational management and Jay Heizer and Barry Render on production. The data collection method uses documentation research. Data processing methods involve reducing, presenting, and drawing conclusions. The method for ensuring the validity of data uses source triangulation. The results of the study indicate that operational management is the process of managing and utilizing resources for the benefit of the company's work services, production is the process of producing goods and services desired by people who work in the company and operational production management is a way of utilizing resources owned to make products that are valuable to the company. This includes planning the production process, which means planning materials and the process of making products, organizing the production process, which means dividing equipment, materials, and labor, directing the production process, which means creating standard operating procedures and product quality, and controlling the production process, which means evaluating work and product results.